Hyperbaric Oxygen Therapy for Managing Cancer Treatment Complications: A Safety Evaluation - Kubra Canarslan Demir; Ahmet Ugur Avci; Munire Kubra Ozgok Kangal; Berrin Ceylan; Selcen Yusra Abayli; Ismail Ozler; Kerim Bora Yilmaz (Medicina)
Background and Objectives: Hyperbaric oxygen therapy (HBOT) has shown promise in managing complications due to cancer treatments, particularly those related to radiotherapy and surgery. Despite its clinical benefits, concerns persist regarding its potential to influence cancer progression. This study aimed to evaluate the safety and clinical outcomes of HBOT in patients with active or previously treated solid tumors. Methods: A retrospective analysis was conducted on patients with solid tumors who underwent at least five HBOT sessions. Comprehensive data, including patient demographics, cancer type, total number of HBOT sessions, imaging findings, and clinical outcomes (recurrence, metastasis, and mortality), were collected. Descriptive statistics and the relationship between the number of HBOT sessions and long-term cancer outcomes were analyzed. Results: This study included 45 patients (median age: 64 years; 60% male) who received a median of 27 HBOT sessions. At initiation, 27.9% of the patients were classified as cured, 53.5% were in remission, and 18.6% had active cancer. Over a median follow-up period of 783 days, 8.7% experienced recurrence, 2.7% had persistent active cancer, and 59.5% had no recurrence. No HBOT-related complications were observed during the course of HBOT. Statistical analyses revealed no significant correlations between the number of HBOT sessions and metastasis (p = 0.213) or mortality (p = 0.881). Conclusions: HBOT appears to be a safe and effective adjunctive therapy for managing complications in patients with solid tumors. No evidence was found to suggest HBOT contributes to tumor progression, recurrence, or metastasis. Future prospective studies with larger cohorts are needed to confirm these results and further evaluate the therapeutic role of HBOT in oncology.